2013
DOI: 10.1038/srep02665
|View full text |Cite
|
Sign up to set email alerts
|

Sb2Se3 under pressure

Abstract: Selected members of the A2B3 (A = Sb, Bi; B = Se, Te) family are topological insulators. The Sb2Se3 compound does not exhibit any topological properties at ambient conditions; a recent high-pressure study, however, indicated that pressure transforms Sb2Se3 from a band insulator into a topological insulator above ~2 GPa; in addition, three structural transitions were proposed to occur up to 25 GPa. Partly motivated by these results, we have performed x-ray diffraction and Raman spectroscopy investigations on Sb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
98
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 52 publications
24
98
1
Order By: Relevance
“…Apparently, the rapid increase of T C of the superconductive phase from 10 GPa to 18 GPa is intimately related to the increase of carrier density, as observed in Bi 2 Te 3 21, Bi 2 Se 3 1322 or Sb 2 Te 3 12 systems. The difference is that all these phenomena of Sb 2 Se 3 occur within the initial ambient crystal structure31 (see Supplementary Fig. S1 online), other than pressure induced crystal structure changes in Bi 2 Te 3 , Bi 2 Se 3 or Sb 2 Te 3 compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the rapid increase of T C of the superconductive phase from 10 GPa to 18 GPa is intimately related to the increase of carrier density, as observed in Bi 2 Te 3 21, Bi 2 Se 3 1322 or Sb 2 Te 3 12 systems. The difference is that all these phenomena of Sb 2 Se 3 occur within the initial ambient crystal structure31 (see Supplementary Fig. S1 online), other than pressure induced crystal structure changes in Bi 2 Te 3 , Bi 2 Se 3 or Sb 2 Te 3 compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The Sb 2 Se 3 crystallizes in space group Pbnm 283132 at ambient condition and sketch of the coordination environment around the Sb1 and Sb2 cations is shown in Supplementary Fig. S2 (a) online.…”
Section: Resultsmentioning
confidence: 99%
“…17 Similarly, TQPT has been claimed in Sb2Se3 (SG: Pnma, Eg = 1 eV) at ~ 2.5 GPa by studying the vibrational phonon and electrical resistivity anomalies together with the first principles calculations, 11,15 though there is also an alternate interpretation suggested. 18 Recently, Ohmura et al, showed that bismuth tellurihalide BiTeBr (S.G: P3m1, Eg = 0.55 eV) undergoes a TQPT at 2.5  3.0 GPa using resistivity and synchrotron XRD measurements under pressure. 10 The above examples provide strong basis for using such indirect methods to study pressure induced TQPT in the SOC systems.…”
Section: Introductionmentioning
confidence: 99%
“…There are two nonequivalent Sb cation sites in this phase. One of the Sb cations is coordinated by seven Se anions and the coordination around the second Sb site can be described as (7+1) with respect to the Se ions [9].…”
Section: Introductionmentioning
confidence: 99%